Technological advancements and the changing face of crop yield stability in Asia - Zsolt Hollósy; Muhammad Imam Ma'ruf; Zsuzsanna Bacsi (Economies, 2023)
Recent technological advancements have revolutionized agriculture in Asia, leading to significant changes in crop yield stability. This study examines the changing face of crop yield stability in Asia resulting from the increasing adoption of innovative technologies in agriculture. Through a review of current research and case studies, the impact of technology-driven changes on yield levels, variability, and predictability is explored. The study applies a yield stability index (YSI) to evaluate the yield stability of six crops in seven Asian countries during two periods (1961-1994 and 1995-2020), comparing the countries, crops, and stability changes between the two segments. The novelty of the research is the application of YSI, which, contrary to usual stability metrics, can distinguish between rare large extreme yields and frequent minor fluctuations, and based on this feature, evaluates the suitability of the prevailing technologies to local environmental conditions. The YSI is used to evaluate the stability of technologies, indicating whether the technologies can respond well to the annual variations of environmental conditions. Positive YSI values indicate stable technologies that can respond well to the annual variations of environmental conditions, and the concept of a well-technologized crop is used for crops in countries with stable positive YSI values, indicating the suitability of the actual crop to the actual geographical environment. These results can guide production technology developments and the introduction or abandonment of certain crops in certain geographical zones, especially regarding the implications of climate change and global warming. This study highlights the transformative power of technology in improving crop yield stability and food security in Asia, while discussing the potential challenges associated with these changes and the need for continued research to address them.
Keywords: 330; agriculture; Asia; crop; technological advancements; yield stability